PENGARUH TRANSPARANSI, AKUNTANBILITAS DAN PARTISIPATIF ANGGARAN TERHADAP EFEKTIVITAS PENGELOLAAN DANA DESA DI MASA PANDEMIK COVID-19 PERSPEKTIF ISLAM (Studi Kasus Pada Desa Srikaton Kecamatan Adiluwih Kabupaten Pringsewu) - Kurniawan, Agus; Putriani, Dewi; Mustofa, Ulul Azmi (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
This study aims to determine the effectiveness of village fund management during the covid-19 pandemic in Srikaton village. The method used in this research is quantitative with a associative analysis approach. The results of the research carried out in the village of Srikaton indicate that government of the village of Srikaton has applied the principles of transparency, accountability, and participatory view of the questionnaire answers submitted to respondents and the presence of balai about the use of village funds during the covid-19 pandemic. The researcher suggests that the village government must apply the principle of transparency, accountability, and participation in order to achieve the effectiveness of village funds management.